Analisis Pelayanan Terhadap Tingkat Kepuasan Mahasiswa Fakultas Ekonomi Universitas Batanghari Jambi (Studi pada Laboratorium Statistik Fakultas Ekonomi Universitas Batanghari Jambi) - Albetris Albetris; Fadil Iskandar (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This research aims to find out how the Service Affects Student Satisfaction at the Faculty of Economics, Batanghari Jambi University. The limitations of the problems in this study are as follows: 1. The variables used in this study are service quality variables that include responsiveness, reliability, assurance, emphaty (empathy), tangibles (direct evidence). And 2. The gap used in this study is the gap between the quality of service perceived and the expected quality of service (service quality gap). The study was analyzed using multiple linear regressions. with results Y= 0.441 + 0.860X. In other words, the regression equation above can be said that the coeffesien regression variable service has a positive direction towards the satisfaction of students of the faculty of economics of batanghari jambi university. The constant or α value of 0.441 means that if the value of variable X (service) is 0 then the variable value Y (satisfaction) will be worth 0.441. The coefficient value (b) of 0.860 means that the value of variable X (service) is positive meaning that if the service variable (X1) rises by 1 unit it will increase variable Y (satisfaction) by 0.860 assuming other variablesits same. and based on statistical tests it is known that there is a significant influence between the service on the satisfaction of service users ( students) computer laboratory of the Faculty of Economics, Batanghari Jambi University, using the t test that is, thitung = 26,106 > t table = 1,984.